Financial performance of commercial banks in the post-reform era: Further evidence from Bangladesh - Robin, I.; Salim, Ruhul; Bloch, Harry (The Economic Society of Australia, 2018)
© 2018 Economic Society of Australia, Queensland This paper examines the financial performance of the commercial banks in Bangladesh in terms of profitability measures before, during and after a period of financial liberalization. Employing a panel data regression framework, the study uses bank-level annual data from major commercial banks in Bangladesh for the period 1983–2012. Empirical results show financial reform has not had significant effect on the return on asset (ROA) or return on equity (ROE) for the banks, but the net interest margin (NIM) has increased. The results further indicate that capital strength and asset quality are the main drivers of profitability. Therefore, an appropriate banking policy aimed at raising capital base and asset quality is vital for ensuring a viable banking sector in Bangladesh.